Cognitive Activation Strategy as an Innovative Teaching Trend to EFL Students in Writing Skill - Ulaywi, Raghad khalaf (Al-Adab Journal, 2021)
Teaching is a difficult task. It requires a leader teacher to build an effective classroom environment. To be an efficient teacher in class, it requires him to create efficient teaching strategies which consider successful ingredients to improve the goodness of education .Successful teaching builds a rational thinking for competent based innovative education. Cognitive activation strategy is one of 21st century teaching strategies which stimulate the process of learning opportunities for students to be educated. This strategy generates successful learning environment where students can grasp a range of meanings. It determines what is happened in high –goodness teaching to prepare teachers innovate this strategy .In addition, teachers can plan for improving the quality of education to guarantee students successful achievement and attain their aims. A good teacher tries to take many roles and presents effective strategies to students to enable them participating in classroom activities and practices. A proficient teacher applies felicitous strategy with learners through sets of intellectual processes thus teaching is considered as processes where one person mediates between another person and the substance of this world to facilitate learning. This is one of the innovative trends of teacher roles. The present study aims at finding out the effect of CA strategy on Iraqi EFL university students’ achievement in writing skill at one of Baghdad private university, namely Al-Sadiq in the academic year 2019/2020.The population of the study were 2nd year college students, male and female, and samples (80 students) were selected as two classes for the experimental groups and one for the control group. The study used quasi-experimental design. Data collection method was taken through testing the students to write well-organized paragraphs in English according to teacher selected topics. The results showed that EFL students face difficulties and commit errors in writing paragraphs in English .Moreover ,they need more training on the mechanics of writing to get rid these problems.